Heterogeneous early immune responses to the S. aureus EapH2 antigen induced by gastrointestinal tract colonisation impact the response to subsequent vaccination. Issue 3 (14th January 2019) - Flaxman, Amy; Yamaguchi, Yuko; van Diemen, Pauline M.; Rollier, Christine; Allen, Elizabeth; Elshina, Elizaveta; Wyllie, David H.
Highlights: Long-term S. aureus experimental gut colonisation can be established in two mouse strains. Colonisation results in detectable serum IgG1 anti- S. aureus antibodies. Responses to individual antigens induced by colonisation vary within genetically identical mice. Immune responses against EapH2 are generated in some, but not other, colonised mice. Natural priming modified the response to subsequent vaccination against EapH2. Abstract: Introduction: S. aureus is a pathogen to which individuals are exposed shortly after birth, with immune responses to S. aureus increasing during childhood. There is marked heterogeneity between the anti- S. aureus immune responses of different humans, the basis of which is not fully understood. Methods: To investigate development of anti- S. aureus immune responses, we studied S. aureus colonised mice under controlled conditions. Mice were either acquired colonised from breeding colonies, or experimentally colonised by exposure to a cage environment which had been sprayed with a S. aureus suspension. Colonisation was monitored by sequential stool sampling, and immunoglobulin levels against both whole fixed S. aureus and individual S. aureus antigens quantified. The immunological impact of colonisation on subsequent vaccination was investigated. Results: Colonised BALB/c and BL/6 mice develop serum anti- S. aureus cell surface IgG1 antibodies. Responses were proportional to the cumulative S. aureus bioburden in the mice, and were higher in BALB/c mice, which have higher colonisation levels, than in C57BL/6 animals. We observed marked variation in the induction of anti-cell surface antibodies, even in genetically identical mice experimentally colonised with the same S. aureus clone. Heterogeneity was also evident when monitoring immune responses to the secreted S. aureus protein EapH2. Approximately 50% of colonised mice developed anti-EapH2 responses (responders); in other mice, responses were not significantly different to those in uncolonised mice (non-responders). Following vaccination with a replication deficient adenovirus expressing EapH2, less anti-EapH2 antibody was generated in non-responder than responder animals. Conclusions: In genetically identical mice, S. aureus colonisation results in all-or-nothing antibody responses against some antigens, including EapH2. For antigens involved in colonisation success by microbes, apparently stochastic early immune responses may impact both vaccine responses and the establishment of an animal-specific microbiome.